James Duff Brown's manual of library economy - Lock R. Northwood (London : Grafton & Co., 1961)
Dealt mainly with broad principles of librarianship and summarized most of the best and vital methods which has been adopted in the field.
Includes index.
kjo 16/01/2019
Loans
Keywords: James, Duff Brown; Library science